2021
DOI: 10.3390/mi12020165
|View full text |Cite
|
Sign up to set email alerts
|

Stiff-to-Soft Transition from Glass to 3D Hydrogel Substrates in Neuronal Cell Culture

Abstract: Over the past decade, hydrogels have shown great potential for mimicking three- dimensional (3D) brain architectures in vitro due to their biocompatibility, biodegradability, and wide range of tunable mechanical properties. To better comprehend in vitro human brain models and the mechanotransduction processes, we generated a 3D hydrogel model by casting photo-polymerized gelatin methacryloyl (GelMA) in comparison to poly (ethylene glycol) diacrylate (PEGDA) atop of SH-SY5Y neuroblastoma cells seeded with 150,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…According to these results, most of the cavities are in connection with each other and only a few of them are separated. This may confirm that the cells, especially the SH-SY5Y cells, are organizing themselves into clusters at first with high cell density [ 61 ]. These clusters are clearly observable on the phase-contrast microscopic images ( Figure 3 , SH-SY5Y day 14).…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…According to these results, most of the cavities are in connection with each other and only a few of them are separated. This may confirm that the cells, especially the SH-SY5Y cells, are organizing themselves into clusters at first with high cell density [ 61 ]. These clusters are clearly observable on the phase-contrast microscopic images ( Figure 3 , SH-SY5Y day 14).…”
Section: Resultsmentioning
confidence: 76%
“…We observed that the tumor cell line proliferated at a higher rate than PDLCs even under standard culture conditions in Petri dishes before seeding them for these experiments. SH-SY5Y cells usually form clusters on three-dimensional hydrogel matrices [ 42 , 56 , 61 ], which can also be seen in Figure 3 ; this behavior can explain the discrepancy between the viability and microscopic results. Clusters can cause insufficient nutrition supply and hampered diffusion, therefore the WST-1 reagent cannot be converted to formazane by the mitochondria since it cannot reach the inner region of the clusters [ 42 ].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, rat cortical cells and neuroblastoma cells (SH-SY5Y) [ 21 ] have already been investigated by us simply by adding hydrogels into the on-chip culture reservoir. To this end, we presented here our additional article on the design and testing of a straightforward concept to evaluate whether 2D seeded cells transition into 3D, when cultured within a hard–soft interface adding a hydrogel atop of the seeded cells [ 22 ]. This concept allows us to assess if neurons are susceptible in surviving in these materials and how they change their morphology and organization upon the change in mechanical cue, i.e., offering a far lower Young’s modulus compared to the glass and multitude of 3D spreading anchoring points for cell interactions within the porous 3D matrix of the hydrogel.…”
mentioning
confidence: 99%